A propylene oxidation catalyst and its preparation process
By preparing the propylene oxidation catalyst composed of MoaXbBicSidCeOf, the shortcomings of the existing catalysts in terms of structural stability and acrolein yield were solved, and efficient acrolein preparation was achieved.
Patent Information
- Application Number
- CN202411930614.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing acrolein catalysts for preparing acrolein oxidation have shortcomings in terms of the structural stability of the catalyst and the yield of acrolein.
A catalyst for preparing acrolein oxidation is provided, which consists of MoaXbBicSidCeOf. X is selected from one or two or three types of iron-cobalt nickel, and is prepared by co-precipitation reaction, drying, granulation and calcination. The catalyst includes nanoparticles, nanorods and irregular particles.
The catalyst has good crystallinity and catalytic activity, which improves the yield of acrolein and the structural stability of the catalyst, and ensures efficient propylene oxidation reaction.
Smart Images

Figure BDA0005210196840000101 
Figure BDA0005210196840000111 
Figure BDA0005210196840000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst production, in particular to a propylene oxidation catalyst and a preparation process thereof. Background Art
[0002] Acrylic acid is an organic compound with the chemical formula C 3 H 4 O 2 , the structural formula is CH 2 =CH-COOH. Acrylic acid is a very important organic chemical raw material and an important derivative of propylene. It is mainly used to produce acrylic esters (such as methyl acrylate, ethyl acrylate, butyl acrylate, etc.), and further produce a variety of acrylic resin products, which can be widely used in coatings, chemical fibers, textiles, leather, adhesives, acrylic rubber and other fields.
[0003] The main methods for preparing acrylic acid include lactic acid dehydration method, high-pressure Rape method, β-propiolactone method, acrylonitrile hydrolysis method, cyanoethanol method, and propylene oxidation method. Lactic acid dehydration method is that lactic acid undergoes intramolecular dehydration reaction in the presence of a catalyst to produce acrylic acid. High-pressure Rape method is that acetylene dissolved in tetrahydrofuran reacts with carbon monoxide and water in the presence of a catalyst composed of nickel bromide and copper bromide to produce acrylic acid. β-propiolactone method is that acetic acid is first cracked into ketene, ketene reacts with anhydrous formaldehyde to produce β-propiolactone, and β-propiolactone is isomerized into acrylic acid under the action of phosphoric acid catalyst. Acrylonitrile hydrolysis method is that acrylonitrile is first hydrolyzed in the presence of sulfuric acid catalyst to produce acrylamide sulfate, and then hydrolyzed in the second step to produce acrylic acid. The cyanoethanol method uses chloroethanol and sodium cyanide as raw materials, first reacts to produce cyanoethanol, and cyanoethanol undergoes hydrolysis reaction in the presence of sulfuric acid to produce acrylic acid. If the hydrolysis reaction is carried out in methanol, methyl acrylate is produced.
[0004] The propylene oxidation process is currently the most widely used acrylic acid preparation process. It is a process in which propylene reacts with oxygen in the air under the action of a catalyst to first generate acrolein, which is then further oxidized to generate acrylic acid. In this acrylic acid preparation process, the first step is to mix propylene, air, and water vapor and react to generate acrolein in the presence of a catalyst.
[0005] Main reaction:
[0006] CH 2 =CHCH 3 +O 2 →CH 2 =CHCHO+H2O
[0007] Side effects:
[0008] 4CH 2 =CHCH 3+15O 2 →6CO+6CO 2 +12H 2 O
[0009] 2CH 2 =CHCH 3 +5O 2 →2CH 3 COOH+2CO 2 +2H 2 O
[0010] The second step is the oxidation of acrolein with air and water vapor in the presence of a catalyst to produce acrylic acid.
[0011] Main reaction:
[0012] 2CH 2 =CHCHO+O 2 →2CH 2 =CHCOOH
[0013] Side effects:
[0014] 4CH 2 =CHCHO+11O 2 →6CO+6CO 2 +8H 2 O
[0015] 4CH 2 =CHCHO+O 2 +H 2 O→4CH 2 =O+4CH 2 CH=O
[0016] Since the process is carried out in steps, that is, propylene is first oxidized to acrolein, and acrolein is then oxidized to acrylic acid, the catalyst and reaction conditions can be selected specifically according to the reaction characteristics of each step, and the product yield is good.
[0017] CN00122609.6 discloses a catalyst for producing acrolein and acrylic acid by catalytic oxidation of propylene using molecular oxygen or a gas vapor containing molecular oxygen in a fixed bed multi-tube reactor.
[0018] Mo a W b Bi c Fe d A e B f C g D h Ox(Ⅰ)
[0019] Wherein Mo is molybdenum; W is tungsten; Bi is bismuth; Fe is iron; A is at least one element selected from cobalt and nickel; B is at least one element selected from phosphorus, antimony, boron, tin, cerium, niobium, lead, chromium and zinc; C is at least one element selected from alkali metals and thallium; D is at least one element selected from silicon, aluminum, titanium and zirconium; O is oxygen.
[0020] CN200810090707.0 discloses an oxide catalyst, a method for preparing acrolein or acrylic acid, and a method for preparing a water-absorbent resin, wherein the oxide catalyst is represented by the following formula (2):
[0021] Mo 12 Bi a Fe b A c B d C e D f O x (2)
[0022] Wherein Mo is molybdenum, Bi is bismuth, Fe is iron, A is an element selected from at least cobalt and nickel, B is an element selected from at least alkali metals, alkaline earth metals and thallium, C is an element selected from at least tungsten, silicon, aluminum, zirconium and titanium; D is an element selected from at least phosphorus, tellurium, antimony, tin, cesium, lead, niobium, manganese, arsenic and zinc, and O is oxygen.
[0023] CN200980124890.4 discloses a catalyst for preparing acrolein and / or acrylic acid, wherein the catalyst is a catalyst for preparing acrolein and / or acrylic acid by gas-phase catalytic oxidation of propylene using a molecular oxygen-containing gas, wherein the catalyst contains a catalytic active component having molybdenum, bismuth and cobalt as essential components, and when measured by X-ray diffraction analysis using Cu-Kα rays, the crystallinity T of the catalytic active component within the range of 2θ=5° to 90° is within the range of 4% to 18%.
[0024] CN201310585695.X discloses a method for preparing acrolein by oxidizing propylene. The raw materials propylene, water and air are preheated in a preheater at 120°C or above and then enter a fixed bed single tube reactor. The salt bath temperature is 300-340°C, the air velocity is 800-2000h-1, and the feed composition is: 8-15 volume % of propylene, 70-74 volume % of air, and 15-21% of water vapor. The fixed bed reactor is equipped with an oxidation catalyst, which contains molybdenum, bismuth, iron, nickel, cobalt and copper elements and is mainly composed of the general formula Mo a Bi b Fe c Ni d Co e Cu f Si h A i Bj O y It is indicated that the catalyst also contains lanthanum magnesium aluminate oxide.
[0025] CN202011105008.6 discloses a catalyst for preparing acrolein by oxidation of propylene, a preparation method and application thereof, and the general formula of the components of the catalyst is: MoBi a Fe b Ni c X d Y e Z f Q g (AlPO 4 ) h O j , wherein X is at least one selected from Mg, Co, Ca, Cu, Zn and Mn; Y is at least one selected from Nb, Sb and W; Z is at least one selected from K, Rb, Na, Li and Cs; Q is at least one selected from La, Ce and Sm.
[0026] CN202211328692.3 discloses an oxidation catalyst, a preparation method and application thereof, and a method for preparing acrolein. The catalyst comprises a catalyst having the general formula MoBi a Fe b X c Y d Z e Q f O j ·g NiMoO 4 wherein X is selected from at least one of Mg, Co, Ca, Cu, Zn and Mn; Y is selected from at least one of Nb, Sb and W; Z is selected from at least one of K, Rb, Na, Li and Cs; and Q is at least one of La, Ce and Sm.
[0027] In the two-step process of preparing acrylic acid by catalytic oxidation of propylene, the first step is to oxidize propylene to produce acrolein. The catalyst used in this step is crucial to the yield of acrolein, and the stability of the catalyst is also very critical. The existing catalysts for oxidizing propylene to produce acrolein have certain problems that need to be improved in terms of the structural stability of the catalyst and the yield of acrolein. Summary of the invention
[0028] In view of the problems in the prior art, the present invention first provides a catalyst for preparing acrolein by oxidation of propylene, which comprises Mo a X b Bi c Si d C e O f, X is selected from one, two or three of iron, cobalt and nickel, and must contain iron, a, b, c, d, e, f are the atomic contents of the corresponding elements, a+b+c+d+e+f=100, 1≤a≤10, 0.1≤b≤5, 0.1≤c≤8, 1≤d≤30, 10≤e≤60, f is the remainder, the catalyst includes nanoparticles, nanorods and irregular particles, and the infrared spectrum is at 1118cm -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 582 cm -1 Display Fe 3 O 4 Stretching vibration peak of tetrahedral Fe-O bond.
[0029] Furthermore, the atomic content of molybdenum is 1.5≤a≤8.0, or 1.8, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, or 7.0.
[0030] Furthermore, the atomic content of iron, cobalt and nickel is 0.15≤b≤4.0, or 0.25, 0.5, 0.75, 1.0, 1.5, 1.8, 2.0, 2.5, 3.0, or 3.5.
[0031] Furthermore, the atomic content of bismuth is 0.12≤c≤5.0, or 0.20, 0.25, 0.5, 0.6, 0.75, 1.0, 1.5, 1.8, 2.0, 2.5, 3.0, 3.5, 4.0.
[0032] Furthermore, the atomic content of silicon is 2≤d≤20, or 2.5, 3.0, 3.5, 4.0, 5.0, 8.0, 10.0, or 15.0.
[0033] Furthermore, the atomic content of carbon is 15≤e≤50, or 20, 25, 30, 35, 40, or 45.
[0034] Furthermore, the particle size of the nanoparticles in the catalyst is 5-80 nm, or 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, or 70 nm.
[0035] Furthermore, the major diameter size of the nanorods in the catalyst is in the range of 60-100 nm, or 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm.
[0036] Furthermore, the short diameter size of the nanorods in the catalyst ranges from 10 to 50 nm, or is 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, or 40 nm.
[0037] Furthermore, the particle size of the irregular particles in the catalyst is less than or equal to 600 nm, or is 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, or 300 nm.
[0038] Furthermore, the infrared spectrum of the catalyst sample is at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 Showing the stretching vibration of the Mo-O-Mo bond.
[0039] Furthermore, the infrared spectrum of the catalyst sample is at 779 cm -1 、694cm -1 Showing Co-O stretching vibration.
[0040] Furthermore, the infrared spectrum of the catalyst sample is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0041] The present invention also provides a process for preparing acrolein catalyst by oxidizing propylene, the composition of which is Mo a X b Bi c Si d C e O f , X is selected from one, two or three of iron, cobalt and nickel, and must contain iron, a, b, c, d, e, f are the atomic contents of the corresponding elements, a+b+c+d+e+f=100, 1≤a≤10, 0.1≤b≤5, 0.1≤c≤8, 1≤d≤30, 10≤e≤60, f is the remainder, the catalyst includes nanoparticles, nanorods and irregular particles, and the preparation process includes:
[0042] Step (1): preparing a raw material solution by dissolving potassium hydroxide or sodium hydroxide and the raw materials of the catalyst in water to prepare a raw material solution;
[0043] Step (2): Coprecipitation reaction
[0044] The raw material solutions of step (1) are mixed and silicon powder is added;
[0045] Carrying out a coprecipitation reaction to obtain a primary material;
[0046] Step (3): Drying and granulation
[0047] The primary material is dried, crushed to obtain powder, and granulated to obtain mesoporous cylindrical particles;
[0048] Step (4): Calcination
[0049] The mesoporous cylindrical particles are calcined to obtain a catalyst for preparing acrolein by oxidizing propylene.
[0050] Furthermore, in step (2), sodium hydroxide or potassium hydroxide solution is added to the molybdenum raw material solution and stirred to obtain a mixed solution A; the bismuth raw material solution is added to the iron, cobalt and nickel raw material solution and stirred to obtain a mixed solution B; and the mixed solution B is added to the mixed solution A and stirred to obtain a mixed solution C.
[0051] Furthermore, in step (3), the drying temperature is 80-150°C, or 90°C, 100°C, 110°C, 120°C, 130°C, or 140°C; the drying time is 10-50h, or 15h, 20h, 25h, 30h, or 40h.
[0052] Furthermore, in step (3), granulation includes a pre-granulation process.
[0053] Furthermore, in step (4), the calcination temperature is 300-600°C, or 350°C, 400°C, 450°C, 500°C, 550°C; the calcination time is 10-50h, or 15h, 20h, 25h, 30h, 40h.
[0054] The invention also provides application of the catalyst in synthesizing aldehydes from olefins.
[0055] Furthermore, the olefin is a C2-C5 olefin, more preferably propylene and / or ethylene or butene.
[0056] The oxidation catalyst of the present invention is used for synthesizing aldehyde (acrolein) from olefin (such as propylene), and has high olefin (such as propylene) conversion rate and high acrolein selectivity.
[0057] The present invention also provides a method for preparing acrolein, which comprises:
[0058] The raw material gas containing propylene and the oxidizing gas containing oxygen are contacted with a catalyst for reaction, wherein the catalyst comprises the oxidation catalyst described in the present invention.
[0059] Furthermore, the temperature of the contact reaction is 300-530°C, preferably 330-380°C, or 350°C, 400°C, 450°C, 480°C, or 500°C.
[0060] Furthermore, the pressure of the contact reaction is 0.01-0.08 MPa, or 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, wherein the pressure is gauge pressure.
[0061] Furthermore, in the contact reaction, the raw gas volume mass space velocity is 800 to 1200 mL / g·h.
[0062] Furthermore, in the contact reaction, the volume ratio of propylene: oxygen-containing oxidizing gas is 1:(5-9).
[0063] Furthermore, in order to make the reaction more stable and controllable, it is preferably carried out in the presence of a diluent gas-phase material, and the raw gas also contains a diluent gas-phase material.
[0064] Beneficial effects of the present invention:
[0065] The catalyst for preparing acrolein by oxidation of propylene is simple in preparation process, has good crystallinity, and has Mo 2 O 3 and SiO 2 The crystalline form has high catalytic activity.
[0066] The catalyst for preparing acrolein by oxidizing propylene shows good composite ability, can improve the dispersion and fixation of active components, make the components more evenly dispersed, and improve the yield of acrolein.
[0067] The catalyst for preparing acrolein by oxidizing propylene has good structural stability, thereby improving the mass transfer and heat transfer performance of the catalyst, so that the catalyst has high acrolein conversion rate and selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is the XRD test diagram of the catalyst in Example 1.
[0069] Figure 2 This is the infrared test image of the catalyst in Example 1.
[0070] Figure 3 This is a SEM test image of the catalyst in Example 1.
[0071] Figure 4 This is the TEM test image of the catalyst in Example 1.
[0072] Figure 5 This is the EDS test chart of the catalyst in Example 1.
[0073] Figure 6 This is the SEM test image of the catalyst in Example 2.
[0074] Figure 7 This is the TEM test image of the catalyst in Example 2.
[0075] Figure 8 This is the EDS test chart of the catalyst in Example 2.
[0076] Fig. 9 This is the TEM test image of the catalyst in Example 3.
[0077] Fig.10 This is the EDS test chart of the catalyst in Example 3.
[0078] Fig.11 This is the TEM test image of the catalyst of Example 4.
[0079] Fig.12 This is the EDS test chart of the catalyst in Example 4. DETAILED DESCRIPTION
[0080] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the following will be combined with the preferred embodiments of the present invention and described in detail as follows.
[0081] 1. XRD test:
[0082] Instrument name: X-ray diffractometer
[0083] Model: D8 ADVANCE
[0084] Test conditions: 10-90°, CU target; wavelength: 1.54 angstroms
[0085] 2. Infrared test:
[0086] Instrument name: Fourier transform infrared spectrometer
[0087] Model: German Bruker VERTEX 70
[0088] Test conditions: Wave number range: 4000-400cm -1 ; Resolution: 2cm -1 ; Number of scans: 32 times.
[0089] 3. SEM test:
[0090] Instrument name: Scanning electron microscope
[0091] Model: Zeiss Sigma 300
[0092] Test conditions: Acceleration voltage: 10kV
[0093] 4. HRTEM test:
[0094] Instrument name: Field emission transmission electron microscope
[0095] Model:TECNAL F20
[0096] Test conditions: Acceleration voltage: 200kV
[0097] 5. EDS test:
[0098] Instrument name: Scanning electron microscope and energy dispersive X-ray fluorescence spectrometer
[0099] The test conditions refer to GB / T 25189-2010 Determination method of quantitative analysis parameters of microbeam analysis scanning electron microscope energy dispersive spectrometer.
[0100] The raw materials used in the catalyst preparation process of the present invention are all purchased commercially.
[0101] Parts in the present invention, unless otherwise specified, are parts by weight.
[0102] The preferred embodiments of the present invention are described below. The preferred embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention.
[0103] Example 1
[0104] A process for preparing a catalyst for preparing acrolein by oxidizing propylene, comprising:
[0105] Step (1): Prepare the raw material solution
[0106] In parts by weight,
[0107] Dissolve 0.15 parts of potassium hydroxide in water and stir to obtain a potassium hydroxide solution;
[0108] Dissolve 160 parts of ammonium molybdate in water and stir to obtain an ammonium molybdate solution;
[0109] Dissolve 50 parts of bismuth nitrate in water, add 12 parts of nitric acid, and stir to obtain a bismuth nitrate solution;
[0110] Dissolve 160 parts of cobalt nitrate and 50 parts of ferric nitrate in water and stir to obtain a cobalt nitrate and ferric nitrate solution;
[0111] Dissolve 25 parts of ammonium nitrate in water and stir to obtain an ammonium nitrate solution;
[0112] Step (2): Coprecipitation reaction
[0113] Adding potassium hydroxide solution to ammonium molybdate solution and stirring to obtain mixed solution A;
[0114] adding the bismuth nitrate solution to the cobalt nitrate and ferric nitrate solutions, and stirring to obtain a mixed solution B;
[0115] Adding mixed solution B to mixed solution A and stirring to obtain mixed solution C;
[0116] Add the ammonium nitrate solution to the mixed solution C, and simultaneously add 50 parts by weight of silicon powder;
[0117] Carrying out a coprecipitation reaction to obtain a primary material;
[0118] Step (3): Drying and granulation
[0119] The primary material is dried at a temperature of 100°C for 40 hours;
[0120] The dried material is crushed to obtain powder, and 100 parts of the powder are added with 120 parts of carbon powder, 10 parts of silicon powder, 30 parts of molybdenum oxide, and 10 parts of silica sol, and granulated to obtain mesoporous cylindrical particles;
[0121] Step (4): Calcination
[0122] The mesoporous cylindrical particles were calcined in a calcination furnace at a temperature of 400° C. for 10 h to obtain a catalyst for preparing acrolein by oxidation of propylene.
[0123] The prepared catalyst was tested, such as Figure 1-5 As shown, Figure 1 Display XRD test results, Figure 2 Display infrared test results, Figure 3 Display SEM test results, Figure 4 Display TEM test results, Figure 5 Displays EDS test results.
[0124] According to the test analysis of the catalyst, it can be determined that the catalyst has good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 30-40nm, the size of the nanorods is about 80×40nm, the size of the irregular particles is 100-250nm, and the overall particle size range is 30-250nm. -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0125] The EDS spectrum analysis results of the catalyst are as follows:
[0126]
[0127] That is, the composition of the catalyst is Mo 3.82 Fe 0.36 Co 1.63 Bi 0.27 Si 8.05 C 40.6 O 45.26 , which does not contain elemental nitrogen N.
[0128] Example 2
[0129] A preparation process for a catalyst for preparing acrolein by oxidizing propylene, which is different from Example 1 in that the weight parts of the raw materials are adjusted to 0.1 parts of potassium hydroxide, 80 parts of ammonium molybdate, 40 parts of bismuth nitrate, 12 parts of nitric acid, 200 parts of cobalt nitrate, 40 parts of iron nitrate, and 25 parts of ammonium nitrate. Ammonia water is added to the coprecipitation reaction, and the pH value of the reaction system is adjusted to carry out the coprecipitation reaction.
[0130] The prepared catalyst was tested, and some of the results are as follows: Figure 6-8 As shown, Figure 6 Display SEM test results, Figure 7 Display TEM test results, Figure 8 Displays EDS test results.
[0131] According to the test analysis of the catalyst, it can be determined that the catalyst has good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 10-35nm, the size of the nanorods is about 80×20nm, the size of the irregular particles is 80-200nm, and the overall particle size range is 10-200nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1Shows the stretching vibration peaks of Bi-O bonds.
[0132] The EDS spectrum analysis results of the catalyst are as follows:
[0133]
[0134] That is, the composition of the catalyst is Mo 1.87 Fe 0.22 Co 0.84 Bi 0.16 Si 5.36 C 59.04 O 32.52 .
[0135] Example 3
[0136] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the weight parts of the raw materials are adjusted. The content of potassium hydroxide is 0.1 parts, the content of ammonium molybdate is 75 parts, the content of bismuth nitrate is 45 parts, the content of nitric acid is 15 parts, the content of cobalt nitrate is 220 parts, the content of iron nitrate is 50 parts, and the content of ammonium nitrate is 30 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0137] The prepared catalyst was tested, and some of the results are as follows: Figure 9-10 As shown, Fig. 9 Display TEM test results, Fig.10 Display EDS test results
[0138] It can be determined that the catalyst has good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 20-35nm, the size of the nanorods is about 90×40nm, the size of the irregular particles is 50-300nm, and the overall particle size range is 20-350nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0139] The EDS spectrum analysis results of the catalyst are as follows:
[0140]
[0141] That is, the composition of the catalyst is Mo 3.46 Fe 0.42 Co 1.84 Bi 0.33 Si 3.24 C 51.50 O 39.21 .
[0142] Example 4
[0143] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the weight parts of the raw materials are adjusted. The content of potassium hydroxide is 0.1 parts, the content of ammonium molybdate is 75 parts, the content of bismuth nitrate is 40 parts, the content of nitric acid is 12 parts, the content of cobalt nitrate is 180 parts, the content of iron nitrate is 38 parts, and the content of ammonium nitrate is 25 parts. Ammonia water is added to the coprecipitation reaction, and the pH value of the reaction system is adjusted to carry out the coprecipitation reaction.
[0144] The prepared catalyst was tested, and some of the results are as follows: Figure 11-12 As shown, Fig.11 Display TEM test results, Fig.12 Display EDS test results
[0145] It can be determined that the catalyst has good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 10-35nm, the size of the nanorods is about 80×20nm, the size of the irregular particles is 80-200nm, and the overall particle size range is 10-200nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0146] The EDS spectrum analysis results of the catalyst are as follows:
[0147]
[0148] That is, the composition of the catalyst is Mo 3.20 Fe 0.32 Co 1.43 Bi 0.25 Si 1.18 C 65.97 O 27.64 .
[0149] Example 5
[0150] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of sodium hydroxide is 0.1 parts, the content of ammonium molybdate is 75 parts, the content of bismuth nitrate is 40 parts, the content of nitric acid is 12 parts, the content of cobalt nitrate is 150 parts, the content of iron nitrate is 38 parts, the content of nickel nitrate is 20 parts by weight, and the content of ammonium nitrate is 25 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0151] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 10-50nm, the size of the nanorods is about 60×30nm, the size of the irregular particles is 80-300nm, and the overall particle size range is 10-300nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm-1 Shows the stretching vibration peaks of Bi-O bonds.
[0152] The EDS spectrum analysis results of the catalyst show that the composition of the catalyst is:
[0153] Mo 3.08 Fe 0.39 Co 1.06 Ni 0.31 Bi 0.23 Si 7.05 C 51.78 O 36.10 .
[0154] Example 6
[0155] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of sodium hydroxide is 0.1 parts, the content of ammonium molybdate is 75 parts, the content of bismuth nitrate is 40 parts, the content of nitric acid is 12 parts, the content of cobalt nitrate is 150 parts, the content of iron nitrate is 38 parts, the content of nickel nitrate is 20 parts by weight, and the content of ammonium nitrate is 25 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0156] In the granulation process, 20 parts of silica powder are used instead of 10 parts of silica powder and 10 parts of silica sol.
[0157] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 30-50nm, the size of the nanorods is about 60×30nm, the size of the irregular particles is 90-400nm, and the overall particle size range is 30-400nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1Shows the stretching vibration peaks of Bi-O bonds.
[0158] Example 7
[0159] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of sodium hydroxide is 0.05 parts, the content of ammonium molybdate is 100 parts, the content of bismuth nitrate is 60 parts, the content of nitric acid is 15 parts, the content of cobalt nitrate is 120 parts, the content of iron nitrate is 30 parts, the content of nickel nitrate is 40 parts by weight, and the content of ammonium nitrate is 50 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0160] In the granulation process, 20 parts of silica sol are used instead of 10 parts of silica powder and 10 parts of silica sol.
[0161] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 35-55nm, the size of the nanorods is about 80×35nm, the size of the irregular particles is 100-400nm, and the overall particle size range is 35-400nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0162] Example 8
[0163] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of sodium hydroxide is 0.5 parts, the content of ammonium molybdate is 200 parts, the content of bismuth nitrate is 60 parts, the content of nitric acid is 15 parts, the content of cobalt nitrate is 180 parts, the content of iron nitrate is 50 parts, and the content of ammonium nitrate is 50 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0164] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 30-60nm, the size of the nanorods is about 70×40nm, the size of the irregular particles is 90-350nm, and the overall particle size range is 30-350nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0165] Example 9
[0166] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of sodium hydroxide is 0.5 parts, the content of ammonium molybdate is 220 parts, the content of bismuth nitrate is 60 parts, the content of nitric acid is 15 parts, the content of cobalt nitrate is 150 parts, the content of ferric chloride is 40 parts, and the content of ammonium nitrate is 50 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0167] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 30-55nm, the size of the nanorods is about 80×30nm, the size of the irregular particles is 100-500nm, and the overall particle size range is 30-500nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 779 cm -1 、694cm -1 Shows Co-O stretching vibration at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0168] Example 10
[0169] A preparation process for a catalyst for preparing acrolein by oxidation of propylene, which differs from Example 1 in that the raw material composition and weight parts are adjusted. The content of potassium hydroxide is 0.5 parts, the content of ammonium molybdate is 210 parts, the content of bismuth subcarbonate is 60 parts, the content of nitric acid is 15 parts, the content of nickel nitrate is 180 parts, the content of iron nitrate is 50 parts, and the content of ammonium nitrate is 50 parts. Ammonia water is added to the coprecipitation reaction, the pH value of the reaction system is adjusted, and the coprecipitation reaction is carried out.
[0170] The prepared catalyst was tested and it was confirmed that the catalyst had good crystallinity and Mo 2 O 3 and SiO 2 The catalyst contains nanoparticles, nanorods and irregular particles. The size of the nanoparticles is about 25-45nm, the size of the nanorods is about 60×30nm, the size of the irregular particles is 80-350nm, and the overall particle size range is 25-350nm. The infrared spectrum analysis of the catalyst sample also shows that the -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 990 cm -1 Shows stretching vibration of the molybdenum oxygen double bond at 797 cm -1 、862cm -1 The stretching vibration of Mo-O-Mo bond is shown at 582 cm -1 Display Fe 3 O 4 The stretching vibration peak of the tetrahedral Fe-O bond is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
[0171] Comparative Example 1
[0172] A preparation process of a catalyst for preparing acrolein by oxidation of propylene, which is different from Example 1 in that silicon micropowder and silica sol are not used in the raw materials for preparing the catalyst.
[0173] Comparative Example 2
[0174] A process for preparing a catalyst for preparing acrolein by oxidation of propylene, which is different from Example 1 in that ferric nitrate is not used in the raw materials for preparing the catalyst.
[0175] Catalyst performance test
[0176] In the following examples, the catalyst evaluation conditions are as follows:
[0177] Reactor: fixed bed single tube reactor, inner diameter 26.0 mm, reactor length 800 mm;
[0178] Catalyst: 180 g;
[0179] Reaction temperature: 350°C;
[0180] Reaction pressure: 0.03MPa (gauge pressure);
[0181] Propylene: air (molar ratio) = 1:7;
[0182] Propylene: water vapor (molar ratio) = 1:1.8;
[0183] Raw gas volume mass space velocity: 1000mL / g·h;
[0184] The reaction product was absorbed by dilute acid at 0°C and analyzed by gas chromatography (Agilent 7890A). The carbon balance was calculated and the data were valid when the carbon balance was (96-104)%.
[0185] Propylene conversion, product yield and selectivity are defined as
[0186] Propylene conversion = 1-(unreacted propylene C moles / total product C moles)
[0187] Yield of a product = moles of C of a product / moles of C of all products
[0188] The catalysts of Examples 1-10 and Comparative Examples 1-2 were subjected to catalytic testing and evaluation, and the results are as follows:
[0189] catalyst Propylene conversion Acrolein yield Example 1 99.5% 85.3% Example 2 99.1% 84.2% Example 3 99.7% 85.0% Example 4 99.5% 84.3% Example 5 98.9% 85.8% Example 6 99.2% 86.3% Example 7 99.1% 85.6% Example 8 98.8% 87.2% Example 9 99.0% 85.8% Example 10 99.4% 85.5% Comparative Example 1 92.5% 74.6% Comparative Example 2 89.5% 75.3%
[0190] The catalysts of Examples 1-10 can still maintain their catalytic activity after 2500 hours of oxidation reaction. It can be seen that the catalyst for preparing acrolein by oxidizing propylene has good catalytic performance, with a propylene conversion rate of more than 98.5% and acrolein selectivity of more than 84.0%.
[0191] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A catalyst for preparing acrolein by oxidation of propylene, comprising: a X b Bi c Si d C e O f , X is selected from one, two or three of iron, cobalt and nickel, and must contain iron, a, b, c, d, e, f are the atomic contents of the corresponding elements, a+b+c+d+e+f=100, 1≤a≤10, 0.1≤b≤5, 0.1≤c≤8, 1≤d≤30, 10≤e≤60, f is the remainder, the catalyst includes nanoparticles, nanorods and irregular particles, and the infrared spectrum is at 1118cm -1 、938cm -1 、905cm -1 Displays Si-O stretching and bending vibrations at 582 cm -1 Shows the stretching vibration peaks of the tetrahedral Fe-O bonds in Fe3O4.
2. The catalyst according to claim 1, characterized in that The particle size of the nanoparticles in the catalyst is 5-80nm.
3. The catalyst according to claim 1, characterized in that The long diameter size of the nanorods in the catalyst ranges from 60 to 100 nm.
4. The catalyst according to claim 1, characterized in that The short diameter size of the nanorods in the catalyst ranges from 10 to 50 nm.
5. The catalyst according to claim 1, characterized in that The infrared spectrum of the catalyst sample is at 495 cm -1 Shows the stretching vibration peaks of Bi-O bonds.
6. A process for preparing acrolein catalyst by oxidation of propylene, the composition of which is Mo a X b Bi c Si d C e O f , X is selected from one, two or three of iron, cobalt and nickel, and must contain iron, a, b, c, d, e, f are the atomic contents of the corresponding elements, a+b+c+d+e+f=100, 1≤a≤10, 0.1≤b≤5, 0.1≤c≤8, 1≤d≤30, 10≤e≤60, f is the remainder, the catalyst includes nanoparticles, nanorods and irregular particles, and the preparation process includes: Step (1): preparing a raw material solution by dissolving potassium hydroxide or sodium hydroxide and the raw materials of the catalyst in water to prepare a raw material solution; Step (2): Coprecipitation reaction The raw material solutions of step (1) are mixed and silicon powder is added; Carrying out a coprecipitation reaction to obtain a primary material; Step (3): Drying and granulation The primary material is dried, crushed to obtain powder, and granulated to obtain mesoporous cylindrical particles; Step (4): Calcination The mesoporous cylindrical particles are calcined to obtain a catalyst for preparing acrolein by oxidizing propylene.
7. The process for preparing a catalyst for preparing acrolein by oxidation of propylene according to claim 6, characterized in that: In step (3), the drying temperature is 80-150°C.
8. The process for preparing a catalyst for preparing acrolein by oxidation of propylene according to claim 6, characterized in that: In step (3), granulation includes a pre-granulation process.
9. Use of the catalyst according to any one of claims 1 to 5 or the catalyst obtained by the preparation process according to any one of claims 6 to 8 in the synthesis of aldehydes from olefins.
10. A method for preparing acrolein, the method comprising: The raw material gas containing propylene and the oxidizing gas containing oxygen are contacted with a catalyst for reaction. The catalyst is the catalyst according to any one of claims 1 to 5 or the catalyst obtained by the preparation process according to any one of claims 6 to 8.
Citation Information
Patent Citations
Oxide catalyst, process for producing acrolein or acrylic acid and process for producing water-absorbent resin
CN101274279A
Catalyst for acrolein and / or acrylic acid production and process for producing acrolein and / or acrylic acid using the catalyst
CN102076411B
A method for preparing acrolein
CN104649876B
Catalyst for preparing acrolein through propylene oxidation as well as preparation method and application of catalyst
CN114425379A
Oxidation catalyst, preparation method and application thereof, and acrolein preparation method
CN117960187A